On Weak Solvability of Boundary Value Problem with Variable Exponent Arising in Nanostructure. (23rd July 2021) - Maadan, Hicham; Askour, Nour Eddine; Messaho, Jamal
Abstract : This work is devoted to study the limit behavior of weak solutions of an elliptic problem with variable exponent, in a containing structure, of an oscillating nanolayer of thickness and periodicity parameter depending on ε . The generalized Sobolev space is constructed, and the epiconvergence method is considered to find the limit problem with interface conditions.